Novel flexible CIGS thin film solar cell
By using magnesium-zinc oxygen alloy film as buffer layer and Ti/TiN composite film as barrier layer in copper indium gallium selenide thin film solar cells, combined with Mo:Na/Mo multi-layer composite film as back electrode, the high-energy photon absorption is solved. The buffer layer is prone to delivery and the diffusion of flexible substrate defects to the absorbing layer affects efficiency, achieving efficient, stable and environmentally friendly solar cell devices.
Patent Information
- Application Number
- CN202411624764.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-18
AI Technical Summary
In spacecraft applications, existing copper indium gallium selenide thin-film solar cells have problems such as low absorption of high-energy photons, easy delivery of the buffer layer, and diffusion of flexible substrate defects into the absorbing layer affects efficiency.
Magnesium-zinc oxygen alloy film is used as the buffer layer and prepared by magnetron sputtering method. The magnesium content is between 23% and 45%, the molar ratio of magnesium and zinc is between 0.3 and 0.8, and the Ti/TiN composite film is used as The barrier layer and the Mo:Na/Mo multi-layer composite film are used as the back electrode to form an efficient copper indium gallium selenide thin film solar cell structure.
It effectively improves the photoelectric conversion efficiency of solar cells, enhances the stability and radiation resistance of battery devices, reduces the preparation cost, and is suitable for efficient power supply applications of spacecraft.
Smart Images

Figure CN119486271A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solar cells, and in particular to a novel flexible copper indium gallium selenide thin-film solar cell. Background Art
[0002] Since the Soviet Union launched the first artificial satellite in 1957, humans have launched more than 6,000 artificial satellites to perform different missions, and the number of spacecraft launched in the future is showing an increasing trend. The power supply aerospace system provides energy and is an indispensable component of the aircraft. At present, the power supply systems available for spacecraft include fuel cells, rechargeable batteries, atomic energy and solar cells. Among them, solar cells, as a renewable and sustainable energy source, can generate electricity on a single machine and are suitable for long-term inner planetary exploration missions. They are the key research direction in the field of power supply for spacecraft.
[0003] Solar cells are heterogeneous structure devices composed of different semiconductor materials stacked on a substrate. The solar cells currently used in spacecraft are mainly silicon solar cells and multi-junction solar cells composed of III-V materials such as germanium, gallium arsenide, indium phosphide, and their alloys. The AlInGaP / AlInGaAs / InGaAs / Ge solar cells produced by Azur Space can achieve an initial photoelectric conversion efficiency of 32%. However, the rigid substrate of multi-junction solar cells is not easy to bend, the weight-to-power ratio is low, the preparation process is complex, and the production cost is very expensive. In order to reduce production costs, silicon-based solar cells have begun to provide power for some aircraft performing short-term missions. The photoelectric conversion efficiency of silicon-based single-junction cells has reached 26.1%. However, the substrate of silicon-based cells is also non-flexible, and its weight-to-power ratio is only 0.38Wg. ~1 , the complex preparation process and long preparation cycle limit large-scale application. In order to meet the needs of more and more space flight missions, it is necessary to develop flexible, high-quality aviation solar cells with lower power and manufacturing cost.
[0004] Copper indium gallium selenide (CIGS) thin film solar cells have high resistance to space radiation and can be prepared at low cost on flexible substrates. They have great application potential in the preparation of solar cells for future aircraft. However, the quality control problem of CIGS absorber layer currently limits the photoelectric conversion efficiency of thin film cells. On the one hand, the diffusion of impurities from flexible substrate to absorber layer increases defects in CIGS thin film. On the other hand, the imbalance of elements in the growth process of CIGS thin film leads to V Se Vacancy and In CuThe generation of substitutional defects. At the same time, the CdS buffer layer film prepared by the chemical water bath method in CIGS thin-film solar cells is easy to deliquesce in the harsh space environment, reducing the service life of the battery device. The above problems have become problems that must be solved for the application of CIGS thin-film batteries in the aviation field.
[0005] In summary, the prior art obviously has inconveniences and defects in practical use, so it is necessary to improve it. Summary of the invention
[0006] In view of the above-mentioned defects, the purpose of the present invention is to provide a new flexible copper indium gallium selenide thin film solar cell, which can solve the problems in the prior art such as low absorption of high-energy photons, easy deliquesce of the buffer layer, and diffusion of flexible substrate defects to the absorption layer affecting the efficiency of CIGS thin film solar cells.
[0007] In order to achieve the above-mentioned object, the present invention provides a novel flexible copper indium gallium selenide thin film solar cell, comprising a barrier layer, a back electrode, an absorption layer, a buffer layer, a high resistance layer, a window layer and a top electrode, wherein the barrier layer, the back electrode, the absorption layer, the buffer layer, the high resistance layer and the window layer are arranged in sequence from the inside to the outside with a stainless steel substrate as the bottom and are closely connected to each other, characterized in that the absorption layer is made of a copper indium gallium selenide thin film, the buffer layer is made of a magnesium zinc oxide alloy thin film, and the magnesium content in the magnesium zinc oxide alloy thin film is between 23% and 45%; The magnesium-zinc-oxygen alloy thin film buffer layer is prepared by sputtering, wherein the molar ratio of magnesium to zinc is between 0.3 and 0.8, and the substrate temperature is between 200 and 330 o C, the sputtering power is 500~700W; The buffer layer is prepared by: 1) adding magnesium oxide to zinc oxide powder, fully mixing and grinding to obtain magnesium zinc oxide alloy powder; 2) high-pressure molding of the magnesium zinc oxide alloy powder, and high-temperature solid-phase sintering to prepare a magnesium zinc oxide alloy sputtering target; 3) sputtering and depositing the target onto the copper indium gallium selenide film to obtain the magnesium zinc oxide alloy film.
[0008] According to a novel flexible copper indium gallium selenide thin film solar cell of the present invention, the barrier layer is a thin film Ti / TiN composite thin film, the thickness of the Ti film in the multilayer thin film is between 10 and 50 nm, the thickness of the TiN film in the multilayer thin film is between 50 and 450 nm, the sputtering pressure is between 0.1 and 0.6 Pa, and the sputtering gas is Ar; Preparation of the barrier layer: magnetron sputtering technology is used to deposit a Ti / TiN composite thin film barrier layer with a thickness of 50-500 nm on a pretreated stainless steel substrate. The sputtering gas is a mixture of Ar and N2, the sputtering pressure is between 0.1 and 0.6 Pa, and the sputtering power is 2 W / cm 2 .
[0009] According to a novel flexible copper indium gallium selenide thin film solar cell of the present invention, the back electrode is a Mo:Na / Mo multilayer composite film, the thickness of the Mo:Na / Mo film in the multilayer film is 500nm, and the thickness of the Ti / TiN / Mo:Na / Mo multilayer structure film is between 300 and 1000nm; Preparation of the back electrode: Using magnetron sputtering technology, a 300-500nm Mo:Na / Mo composite film back electrode is deposited on the barrier layer; the sputtering gas is argon, the sputtering pressure is 10sccm, and the sputtering power is 2W / cm 2 .
[0010] According to a novel flexible copper indium gallium selenide thin film solar cell of the present invention, the absorption layer is composed of a low-temperature copper indium gallium selenide absorption layer with a thickness of 0-80nm and a high-temperature copper indium gallium selenide absorption layer with a thickness of 1800-2100nm, and the low-temperature copper indium gallium selenide absorption layer is attached to the back electrode, and the high-temperature copper indium gallium selenide absorption layer is located outside the low-temperature copper indium gallium selenide absorption layer; Preparation of the absorption layer: first deposit a 0-80nm low-temperature copper indium gallium selenide absorption layer on the back electrode at room temperature, then heat it to 550-600 o C deposits a 1800~2100nm high-temperature copper indium gallium selenide absorber layer.
[0011] According to a novel flexible copper indium gallium selenide thin film solar cell of the present invention, the high resistance layer is prepared by using a magnetron sputtering method to prepare a layer of intrinsic zinc oxide high resistance layer with a thickness of 80-120nm on the buffer layer, and the sputtering gas is one of Ar and N2 or a mixture of the two.
[0012] According to a novel flexible copper indium gallium selenide thin film solar cell of the present invention, the preparation of the window layer: a layer of aluminum-doped zinc oxide window layer with a thickness of 200-500nm is prepared on the high resistance layer by magnetron sputtering, and the sputtering gas is one of Ar and N2 or a mixture of the two.
[0013] According to a novel flexible copper indium gallium selenide thin film solar cell of the present invention, the substrate is a flexible stainless steel sheet with a thickness not exceeding 50 μm, and the substrate is cleaned by: initial cleaning with a roller brush and a cleaning agent, secondary washing with deionized water under ultrasonic waves, and finally drying the substrate with a hot air knife.
[0014] According to a novel flexible copper indium gallium selenide thin film solar cell of the present invention, the absorption layer is made by sputtering a copper indium gallium selenide composite single target, and the molar ratio of the copper, indium, gallium and selenium target materials is 22:18:8:52.
[0015] According to a novel flexible copper indium gallium selenide thin film solar cell of the present invention, a mixed gas of hydrogen and argon is introduced during the sputtering of the copper indium gallium selenide absorption layer, and the introduced hydrogen is 4% of the argon flow rate.
[0016] According to a novel flexible copper indium gallium selenide thin film solar cell of the present invention, the sputtering method used to prepare the magnesium zinc oxygen alloy thin film buffer layer is one or more of direct current sputtering, radio frequency sputtering and magnetron sputtering.
[0017] The purpose of the present invention is to provide a flexible copper indium gallium selenide thin film solar cell with a magnesium zinc oxide alloy film as a buffer layer, and the functional layers of the solar cell device from the barrier layer to the top aluminum-doped zinc oxide window layer are prepared by single-target magnetron sputtering technology. A multilayer composite Mo back electrode is prepared by adjusting the titanium target sputtering process and the sequential sputtering of Mo:Na and Mo targets. The multilayer composite film can effectively balance the compressive strain between the stainless steel substrate and the molybdenum electrode while blocking the diffusion of substrate impurity particles to the absorption layer, which is conducive to the preparation of high-efficiency battery devices. The magnesium zinc oxide prepared by magnetron sputtering replaces the CdS buffer layer film prepared by the traditional chemical water bath method. The prepared device can absorb high-energy photons and solve the problems of easy deliquesce and radiation resistance in the harsh space environment. The present invention can effectively control the microstructure of the absorption layer, realize the preparation of copper indium gallium selenide thin film solar cells with high mass-to-power ratio on flexible substrates, and the stability and photoelectric conversion efficiency of the battery device are high, and it has broad application prospects in the field of solar cells for spacecraft. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a schematic diagram of the structure of a CIGS solar cell; Figure 2 is the XRD pattern of the MgZnO thin films of Examples 1 to 5; Figure 3 is the half-height width of the diffraction peak of the 002 crystal plane of the MgZnO thin film of Examples 1 to 5; Figure 4 is the UV-visible transmission spectra of the MgZnO thin films of Examples 1 to 5; Figure 5 is the optical band gap of the MgZnO thin films of Examples 1 to 5. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described in detail. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0020] The present invention provides a flexible copper indium gallium selenide thin film solar cell with a magnesium zinc oxygen alloy thin film as a buffer layer, comprising a barrier layer, a back electrode, an absorption layer, a buffer layer, a high resistance layer, a window layer and a top electrode, wherein the barrier layer, the back electrode, the absorption layer, the buffer layer, the high resistance layer and the window layer are arranged in sequence from the inside to the outside with a stainless steel substrate as the bottom and are closely connected to each other.
[0021] The barrier layer is a thin film Ti / TiN composite film, the thickness of the Ti film in the multilayer film is between 10 and 50 nm, the thickness of the TiN film in the multilayer film is between 50 and 450 nm, the sputtering pressure is between 0.1 and 0.6 Pa, and the sputtering gas is Ar; the substrate is a flexible stainless steel sheet with a thickness not exceeding 50 μm, and the cleaning method of the substrate is: initial cleaning with a roller brush and a cleaning agent, secondary rinsing with deionized water under ultrasonic wave, and finally drying the substrate with a hot air knife.
[0022] The back electrode is a Mo:Na / Mo multilayer composite film, the thickness of the Mo:Na / Mo film in the multilayer film is 500nm, and the thickness of the Ti / TiN / Mo:Na / Mo multilayer structure film is between 300 and 1000nm.
[0023] The absorption layer is made of copper indium gallium selenide film, which is composed of a low-temperature copper indium gallium selenide absorption layer with a thickness of 0~80nm and a high-temperature copper indium gallium selenide absorption layer with a thickness of 1800~2100nm. The low-temperature copper indium gallium selenide absorption layer is attached to the back electrode, and the high-temperature copper indium gallium selenide absorption layer is located on the outside of the low-temperature copper indium gallium selenide absorption layer. The absorption layer is made by sputtering a copper indium gallium selenide composite single target, and the molar ratio of copper, indium, gallium and selenium target materials is 22:18:8:52.
[0024] The buffer layer is made of a magnesium-zinc-oxygen alloy film, and the magnesium content in the magnesium-zinc-oxygen alloy film is between 23% and 45%.
[0025] Preparation of barrier layer: magnetron sputtering technology is used to deposit a Ti / TiN composite film barrier layer with a thickness of 50~500nm on the pretreated stainless steel substrate. The sputtering gas is a mixture of Ar and N2, the sputtering pressure is between 0.1~0.6Pa, and the sputtering power is 2W / cm 2 .
[0026] Preparation of back electrode: magnetron sputtering technology is used to deposit 300~500nm Mo:Na / Mo composite film back electrode on the barrier layer; the sputtering gas is argon, the sputtering pressure is 10sccm, and the sputtering power is 2W / cm 2 .
[0027] Preparation of the absorption layer: First, a 0~80nm low-temperature copper indium gallium selenide absorption layer is deposited on the back electrode at room temperature, and then the temperature is raised to 550~600 oC deposits a high-temperature copper indium gallium selenide absorption layer of 1800-2100 nm. During the sputtering of the copper indium gallium selenide absorption layer, a mixed gas of hydrogen and argon is introduced, and the hydrogen introduced is 4% of the argon flow rate.
[0028] The buffer layer is prepared by: 1) adding magnesium oxide to zinc oxide powder, fully mixing and grinding to obtain magnesium zinc oxide alloy powder, wherein the molar ratio of magnesium to zinc is between 0.3 and 0.8; 2) high pressure molding of the magnesium zinc oxide alloy powder, and high temperature solid phase sintering to prepare a magnesium zinc oxide alloy sputtering target; 3) sputtering and depositing the target onto a copper indium gallium selenide film at a substrate temperature of 200 to 330 o C, the sputtering power is 500~700W, and a magnesium-zinc-oxygen alloy film is obtained.
[0029] Preparation of high resistance layer: A layer of intrinsic zinc oxide high resistance layer with a thickness of 80-120 nm is prepared on the buffer layer by magnetron sputtering, and the sputtering gas is one of Ar and N2 or a mixture of the two.
[0030] Preparation of window layer: A 200-500 nm thick aluminum-doped zinc oxide window layer is prepared on the high-resistance layer by magnetron sputtering, and the sputtering gas is one of Ar and N2 or a mixture of the two.
[0031] As a preferred manner, the sputtering method used in preparing the Mg-Zn-O alloy thin film buffer layer is one or more of direct current sputtering, radio frequency sputtering and magnetron sputtering.
[0032] Example 1 The preparation method of the battery comprises the following steps: Step 1, substrate cleaning: select a SS430BA stainless steel sheet with a thickness of 50 μm, first perform an initial cleaning by means of a roller brush and a cleaning agent, then rinse with deionized water under ultrasonic conditions, and then dry the substrate with a hot air knife at 80°C.
[0033] Step 2: Preparation of barrier layer: magnetron sputtering target material is used, with a sputtering power of 2W / cm 2 The sputtering gas was first argon with a gas flow rate of 20 sccm and a sputtering pressure of 0.4 Pa to prepare a 50 nm Ti film; then a mixed gas of argon and nitrogen was introduced with a gas flow rate of 10 sccm and a sputtering pressure of 0.4 Pa to prepare a 450 nm TiN composite film.
[0034] Step three, preparation of the back electrode: use magnetron sputtering target to sputter a molybdenum sodium target with a molar ratio of 5% sodium molybdate to prepare a 200nm molybdenum sodium film, wherein the argon flow rate is 20sccm, the sputtering pressure is 0.4Pa, and the sputtering power is 2W / cm2; then replace the sputtering target in a vacuum environment and use magnetron sputtering to deposit a 300nm molybdenum film on the molybdenum sodium film.
[0035] Step 4: Preparation of CIGS absorption layer: hydrogen and argon are introduced during the sputtering process, where the ratio of hydrogen to argon is 4%, the sputtering pressure is 0.5 Pa, the mixed gas flow rate is 20 sccm, and the sputtering power is 2.2 W / cm 2 , the thickness of the absorption layer film is 2μm.
[0036] Step 5, buffer layer preparation: Magnetron sputtering is used to sputter a magnesium zinc oxide target with a molar ratio of Mg to Zn of 0.3 to prepare a 50nm magnesium zinc oxide film, wherein the sputtering gas is Ar, the sputtering pressure is 0.5Pa, and the sputtering power is 600W.
[0037] Step 6, preparation of high resistance layer: Use magnetron sputtering of intrinsic zinc oxide target to prepare a 100nm zinc oxide high resistance layer on the surface of the buffer layer. The sputtering gas is argon, the gas flow rate is 15sccm, the sputtering pressure is 0.4Pa, and the sputtering power is 100W.
[0038] Step seven, window layer preparation: Use magnetron sputtering of aluminum-doped zinc oxide target to prepare a 400nm front electrode window layer on the surface of the high-resistance layer. The sputtering gas is argon, the gas flow rate is 15sccm, the gas sputtering pressure is 0.4pa, and the sputtering power is 500W.
[0039] Step 8: Preparation of top electrode: Ni and Al are evaporated on the battery surface in sequence by vacuum evaporation, and partially blocked by a mask plate to form a grid electrode. The obtained samples are characterized, and the results are as follows: Figures 1 to 5 And as shown in Table 1.
[0040] Example 2 The preparation method of the battery comprises the following steps: Step 1, substrate cleaning: select a SS430BA stainless steel sheet with a thickness of 50 μm, firstly perform a primary cleaning by means of a roller brush and a cleaning agent, then rinse with deionized water under ultrasonic conditions, and then dry the substrate with a hot air knife at 80°C; Step 2: Preparation of barrier layer: magnetron sputtering target material is used, with a sputtering power of 2W / cm 2The sputtering gas was first argon with a gas flow rate of 20 sccm and a sputtering pressure of 0.4 Pa to prepare a 50 nm Ti film; then a mixed gas of argon and nitrogen was introduced with a gas flow rate of 10 sccm and a sputtering pressure of 0.4 Pa to prepare a 450 nm TiN composite film; Step three, preparation of the back electrode: use magnetron sputtering target to sputter a molybdenum sodium target with a molar ratio of 5% sodium molybdate to prepare a 200nm molybdenum sodium film, wherein the argon flow rate is 20sccm, the sputtering pressure is 0.4Pa, and the sputtering power is 2W / cm2; then replace the sputtering target in a vacuum environment and use magnetron sputtering to deposit a 300nm molybdenum film on the molybdenum sodium film.
[0041] Step 4: Preparation of CIGS absorption layer: Hydrogen and argon are introduced during the sputtering process, where the hydrogen / argon ratio is 4%, the sputtering pressure is 0.5Pa, the mixed gas flow rate is 20sccm, and the sputtering power is 2.2W / cm 2 ,The thickness of the absorption layer film is 2μm.
[0042] Step five, the buffer layer preparation: using magnetron sputtering method sputtering Mg and Zn molar ratio of 0.45 magnesium zinc oxide target, preparing 50nm magnesium zinc oxide film, wherein the sputtering gas is Ar, the sputtering pressure is 0.5Pa, the sputtering power is 600W; Step 6, preparation of high resistance layer: using magnetron sputtering of intrinsic zinc oxide target material, a 100nm zinc oxide high resistance layer is prepared on the surface of the buffer layer, the sputtering gas is argon, the gas flow rate is 15sccm, the sputtering pressure is 0.4Pa, and the sputtering power is 100W; Step seven, preparation of window layer: prepare a 400nm front electrode window layer on the surface of the high resistance layer by magnetron sputtering of aluminum-doped zinc oxide target. The sputtering gas is argon, the gas flow rate is 15sccm, the gas sputtering pressure is 0.4Pa, and the sputtering power is 500W.
[0043] Step 8: Preparation of top electrode: Ni and Al are evaporated on the battery surface in sequence by vacuum evaporation, and partially blocked by a mask plate to form a grid electrode. The obtained samples are characterized, and the results are as follows: Figures 1 to 5 And as shown in Table 1.
[0044] Example 3 The method for preparing the battery comprises the following steps: Step 1, substrate cleaning: select a SS430BA stainless steel sheet with a thickness of 50 μm, firstly perform the initial cleaning by means of a roller brush and a cleaning agent, then rinse with deionized water by ultrasonic wave, and then dry the substrate with a hot air knife at 80°C; Step 2: Preparation of barrier layer: magnetron sputtering target material is used, with a sputtering power of 2W / cm 2 The sputtering gas was first argon with a gas flow rate of 20 sccm and a sputtering pressure of 0.4 Pa to prepare a 50 nm Ti film; then a mixed gas of argon and nitrogen was introduced with a gas flow rate of 10 sccm and a sputtering pressure of 0.4 Pa to prepare a 450 nm TiN composite film; Step 3: Preparation of back electrode: Sputtering a molybdenum sodium target with a molar ratio of 5% sodium molybdate by magnetron sputtering target to prepare a 200nm molybdenum sodium film, wherein the argon flow rate is 20sccm, the sputtering pressure is 0.4Pa, and the sputtering power is 2W / cm 2 ; Then, the sputtering target is replaced in a vacuum environment, and a 300nm molybdenum film is deposited on the molybdenum-sodium film by magnetron sputtering.
[0045] Step 4: Preparation of CIGS absorption layer: Hydrogen and argon are introduced during the sputtering process, where the hydrogen / argon ratio is 4%, the sputtering pressure is 0.5Pa, the mixed gas flow rate is 20sccm, and the sputtering power is 2.2W / cm 2 , the absorption layer film thickness is 2μm.
[0046] Step 5, buffer layer preparation: magnetron sputtering is used to sputter a magnesium zinc oxide target with a molar ratio of Mg to Zn of 0.56 to prepare a 50 nm magnesium zinc oxide film, wherein the sputtering gas is Ar, the sputtering pressure is 0.5 Pa, and the sputtering power is 600 W.
[0047] Step 6, preparation of high resistance layer: Use magnetron sputtering of intrinsic zinc oxide target to prepare a 100nm zinc oxide high resistance layer on the surface of the buffer layer. The sputtering gas is argon, the gas flow rate is 15sccm, the sputtering pressure is 0.4pa, and the sputtering power is 100W.
[0048] Step seven, preparation of window layer: prepare a 400nm front electrode window layer on the surface of the high resistance layer by magnetron sputtering of aluminum-doped zinc oxide target. The sputtering gas is argon, the gas flow rate is 15sccm, the gas sputtering pressure is 0.4Pa, and the sputtering power is 500W.
[0049] Step 8, top electrode preparation: Ni and Al are evaporated on the battery surface in sequence by vacuum evaporation, and partially blocked by a mask plate to form a grid electrode. The obtained samples are characterized, and the results are as follows Figures 1 to 5 And as shown in Table 1.
[0050] Example 4 The method for preparing the battery comprises the following steps: Step 1, substrate cleaning: select a SS430BA stainless steel sheet with a thickness of 50 μm, first perform an initial cleaning by means of a roller brush and a cleaning agent, then rinse with deionized water under ultrasonic conditions, and then dry the substrate with a hot air knife at 80°C.
[0051] Step 2: Preparation of barrier layer: magnetron sputtering target material is used, with a sputtering power of 2W / cm 2 The sputtering gas was first argon with a gas flow rate of 20 sccm and a sputtering pressure of 0.4 Pa to prepare a 50nm Ti film; then a mixed gas of argon and nitrogen was introduced with a gas flow rate of 10 sccm and a sputtering pressure of 0.4 Pa to prepare a 450nm TiN composite film.
[0052] Step three, preparation of the back electrode: use magnetron sputtering target to sputter a molybdenum sodium target with a molar ratio of 5% sodium molybdate to prepare a 200nm molybdenum sodium film, wherein the argon flow rate is 20sccm, the sputtering pressure is 0.4Pa, and the sputtering power is 2W / cm2; then replace the sputtering target in a vacuum environment and use magnetron sputtering to deposit a 300nm molybdenum film on the molybdenum sodium film.
[0053] Step 4: Preparation of CIGS absorption layer: Hydrogen and argon are introduced during the sputtering process, where the hydrogen / argon ratio is 4%, the sputtering pressure is 0.5Pa, the mixed gas flow rate is 20sccm, and the sputtering power is 2.2W / cm 2 , the absorption layer film thickness is 2μm.
[0054] Step 5, buffer layer preparation: magnetron sputtering is used to sputter a magnesium zinc oxide target with a molar ratio of Mg to Zn of 0.59 to prepare a 50nm magnesium zinc oxide film, wherein the sputtering gas is Ar, the sputtering pressure is 0.5Pa, and the sputtering power is 600W.
[0055] Step 6, preparation of high resistance layer: Use magnetron sputtering of intrinsic zinc oxide target to prepare a 100nm zinc oxide high resistance layer on the surface of the buffer layer. The sputtering gas is argon, the gas flow rate is 15sccm, the sputtering pressure is 0.4Pa, and the sputtering power is 100W.
[0056] Step seven, preparation of window layer: prepare a 400nm front electrode window layer on the surface of the high resistance layer by magnetron sputtering of aluminum-doped zinc oxide target. The sputtering gas is argon, the gas flow rate is 15sccm, the gas sputtering pressure is 0.4Pa, and the sputtering power is 500W.
[0057] Step 8: Preparation of top electrode: Ni and Al are evaporated on the battery surface in sequence by vacuum evaporation, and partially blocked by a mask plate to form a grid electrode. The obtained samples are characterized, and the results are as follows: Figures 1 to 5 And as shown in Table 1.
[0058] Example 5 The preparation method of the battery comprises the following steps: Step 1, substrate cleaning: select a SS430BA stainless steel sheet with a thickness of 50 μm, first perform an initial cleaning by means of a roller brush and a cleaning agent, then rinse with deionized water under ultrasonic conditions, and then dry the substrate with a hot air knife at 80°C.
[0059] Step 2: Preparation of barrier layer: magnetron sputtering target material is used, with a sputtering power of 2W / cm 2 The sputtering gas was first argon with a gas flow rate of 20 sccm and a sputtering pressure of 0.4 Pa to prepare a 50nm Ti film; then a mixed gas of argon and nitrogen was introduced with a gas flow rate of 10 sccm and a sputtering pressure of 0.4 Pa to prepare a 450nm TiN composite film.
[0060] Step three, preparation of the back electrode: use magnetron sputtering target to sputter a molybdenum sodium target with a molar ratio of 5% sodium molybdate to prepare a 200nm molybdenum sodium film, wherein the argon flow rate is 20sccm, the sputtering pressure is 0.4Pa, and the sputtering power is 2W / cm2; then replace the sputtering target in a vacuum environment and use magnetron sputtering to deposit a 300nm molybdenum film on the molybdenum sodium film.
[0061] Step 4: Preparation of CIGS absorption layer: Hydrogen and argon are introduced during the sputtering process, where the hydrogen / argon ratio is 4%, the sputtering pressure is 0.5Pa, the mixed gas flow rate is 20sccm, and the sputtering power is 2.2W / cm 2 , the thickness of the absorption layer film is 2μm.
[0062] Step 5, buffer layer preparation: magnetron sputtering is used to sputter a magnesium zinc oxide target with a molar ratio of Mg to Zn of 0.82 to prepare a 50nm magnesium zinc oxide film, wherein the sputtering gas is Ar, the sputtering pressure is 0.5Pa, and the sputtering power is 600W.
[0063] Step 6, preparation of high resistance layer: Use magnetron sputtering of intrinsic zinc oxide target to prepare a 100nm zinc oxide high resistance layer on the surface of the buffer layer. The sputtering gas is argon, the gas flow rate is 15sccm, the sputtering pressure is 0.4Pa, and the sputtering power is 100W.
[0064] Step seven, preparation of window layer: prepare a 400nm front electrode window layer on the surface of the high resistance layer by magnetron sputtering of aluminum-doped zinc oxide target. The sputtering gas is argon, the gas flow rate is 15sccm, the gas sputtering pressure is 0.4Pa, and the sputtering power is 500W.
[0065] Step 8: Preparation of top electrode: Ni and Al are evaporated on the battery surface in sequence by vacuum evaporation, and partially blocked by a mask plate to form a grid electrode. The obtained samples are characterized, and the results are as follows: Figures 1 to 5 And as shown in Table 1.
[0066] Comparative Example The preparation method of the battery comprises the following steps: Step 1, substrate cleaning: select a SS430BA stainless steel sheet with a thickness of 50 μm, first perform an initial cleaning by means of a roller brush and a cleaning agent, then rinse with deionized water by ultrasonic wave, and then dry the substrate with a hot air knife at 80°C.
[0067] Step 2: Preparation of barrier layer: magnetron sputtering target material is used, with a sputtering power of 2W / cm 2 The sputtering gas was first Ar with a gas flow rate of 20 sccm and a sputtering pressure of 0.4 Pa to prepare a 50 nm Ti film; then a mixed gas of argon and nitrogen was introduced with a gas flow rate of 10 sccm and a sputtering pressure of 0.4 Pa to prepare a 450 nm TiN composite film.
[0068] Step three, preparation of the back electrode: use magnetron sputtering target to sputter a molybdenum sodium target with a molar ratio of 5% sodium molybdate to prepare a 200nm molybdenum sodium film, wherein the argon flow rate is 20sccm, the sputtering pressure is 0.4Pa, and the sputtering power is 2W / cm2; then replace the sputtering target in a vacuum environment and use magnetron sputtering to deposit a 300nm molybdenum film on the molybdenum sodium film.
[0069] Step 4: Preparation of CIGS absorption layer: Hydrogen and argon are introduced during the sputtering process, where the hydrogen / argon ratio is 4%, the sputtering pressure is 0.5Pa, the mixed gas flow rate is 20sccm, and the sputtering power is 2.2W / cm 2 , the absorption layer film thickness is 2μm.
[0070] Step 5, preparation of buffer layer: first, dissolve 0.4g of cadmium acetate in 50mL of deionized water, dissolve 0.882g of sodium citrate in 20mL of deionized water, and dissolve 1.9g of thiourea in 40mL of deionized water. Use a polytetrafluoroethylene magnet to rotate and stir until all the powders are dissolved. Add the above-mentioned easily mixed gold in 10mL of ammonia water, stir evenly and put it into a reaction container. Place the container in a 75°C water bath, react for 10 minutes, take it out, wash it with deionized water and blow it dry. Control the thickness of the buffer layer by controlling the reaction time. Use a chemical water bath for 10 minutes to prepare a 50nm thick cadmium sulfide buffer layer on the surface of the CIGS absorption layer prepared in step 4.
[0071] Step 6, preparation of high resistance layer: Use magnetron sputtering of intrinsic zinc oxide target to prepare a 100nm zinc oxide high resistance layer on the surface of the buffer layer. The sputtering gas is argon, the gas flow rate is 15sccm, the sputtering pressure is 0.4Pa, and the sputtering power is 100W.
[0072] Step seven, preparation of window layer: prepare a 400nm front electrode window layer on the surface of the high resistance layer by magnetron sputtering of aluminum-doped zinc oxide target. The sputtering gas is argon, the gas flow rate is 15sccm, the gas sputtering pressure is 0.4Pa, and the sputtering power is 500W.
[0073] Step 8: Preparation of top electrode: Ni and Al are evaporated on the battery surface in sequence by vacuum evaporation, and partially shielded by a mask plate to form a grid electrode. The obtained samples are characterized, and the results are shown in Table 1.
[0074] The best technical means in the prior art is shown in the comparative example, in which a cadmium sulfide buffer layer is prepared on the surface of the absorption layer by a water bath. Due to the high toxicity of cadmium, air and food contaminated by cadmium are seriously harmful to the human body, and the metabolism is slow in the human body. This step is cumbersome and has certain risks. Although the solar cell with a cadmium sulfide buffer layer has good performance, the risk and cost are high in the preparation process. The present invention provides a technical solution for preparing a buffer layer with magnesium zinc oxide instead of cadmium sulfide, and through experimental selection, when the magnesium content in the magnesium-zinc-oxygen alloy film is between 23% and 45%, and the molar ratio of magnesium to zinc is between 0.3 and 0.8, the performance of the solar cell produced in all aspects can reach the performance of the solar cell with a buffer layer made of cadmium sulfide, thereby producing a more environmentally friendly and safe technical means.
[0075] Table 1 Performance parameters of magnesium zinc oxide buffer layer with different Mg contents and comparative CIGS solar cells
[0076] Embodiment 1 to Embodiment 5 The optical band gap of the magnesium zinc oxide film is controlled by adjusting the Mg content in the magnesium zinc oxide buffer layer, such as Figure 5As shown in the figure, the optical band of the magnesium zinc oxide buffer layer increases with the increase of Mg content. The high optical band gap of the absorption layer increases the transmission of the solar spectrum, promotes the absorption of high-energy photons by the CIGS absorption layer, and improves the open circuit voltage of the thin-film battery. At the same time, the energy band bending between the magnesium zinc oxide buffer layer and the CIGS absorption layer is adjusted with the increase of the buffer layer band gap, which can effectively promote the transmission of carriers, inhibit interface recombination, and improve the open circuit voltage of thin-film solar cells. The joint increase of open circuit voltage and short-circuit current makes the battery efficiency and mass-to-power ratio continue to increase in the process of increasing the optical band gap from 3.64eV to 3.88eV. Further increasing the Mg content in the film will destroy the lattice structure of the magnesium zinc oxide film with ZnO as the main body, reduce the lattice quality, increase the recombination probability during carrier transmission, and reduce the battery efficiency.
[0077] In summary, by comparing the data of various embodiments with the comparative examples, it can be concluded that the performance of solar cells made of magnesium zinc oxide as a buffer layer has reached the performance standard of solar cells made of cadmium sulfide as a buffer layer in the prior art, and can further replace the traditional solar cells made of cadmium sulfide as a buffer layer.
[0078] The present invention prepares a multilayer composite Mo back electrode by adjusting the titanium target sputtering process and the sequential sputtering of Mo:Na and Mo targets. The multilayer composite film can effectively balance the compressive strain between the stainless steel substrate and the molybdenum electrode while blocking the diffusion of substrate impurity particles into the absorption layer, which is conducive to the preparation of high-efficiency battery devices. The magnesium zinc oxide prepared by magnetron sputtering replaces the CdS buffer layer film prepared by the traditional chemical water bath method. The prepared device can absorb high-energy photons and solve the problems of easy deliquesce and radiation resistance in the harsh space environment. The present invention can effectively control the microstructure of the absorption layer and realize the preparation of high-quality and high-power copper indium gallium selenide thin film solar cells on flexible substrates. The battery device has high stability and photoelectric conversion efficiency, and has broad application prospects in the field of solar cells for spacecraft.
[0079] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art may make various corresponding changes and modifications based on the present invention, but these corresponding changes and modifications should all fall within the scope of protection of the claims attached to the present invention.
Claims
1. A novel flexible copper indium gallium selenide thin film solar cell, comprising a barrier layer, a back electrode, an absorption layer, a buffer layer, a high resistance layer, a window layer and a top electrode, wherein the barrier layer, the back electrode, the absorption layer, the buffer layer, the high resistance layer and the window layer are arranged in sequence from the inside to the outside with a stainless steel substrate as the bottom and are closely connected to each other, characterized in that: The absorption layer is made of a copper indium gallium selenide film, and the buffer layer is made of a magnesium zinc oxide alloy film, wherein the magnesium content in the magnesium zinc oxide alloy film is between 23% and 45%; The magnesium-zinc-oxygen alloy thin film buffer layer is prepared by sputtering, wherein the molar ratio of magnesium to zinc is between 0.3 and 0.8, and the substrate temperature is between 200 and 330 o C, the sputtering power is 500~700W; The buffer layer is prepared by: 1) adding magnesium oxide to zinc oxide powder, fully mixing and grinding to obtain magnesium zinc oxide alloy powder; 2) high-pressure molding of the magnesium zinc oxide alloy powder, and high-temperature solid-phase sintering to prepare a magnesium zinc oxide alloy sputtering target; 3) sputtering and depositing the target onto the copper indium gallium selenide film to obtain the magnesium zinc oxide alloy film.
2. A novel flexible copper indium gallium selenide thin film solar cell according to claim 1, characterized in that: The barrier layer is a thin film Ti / TiN composite film, the thickness of the Ti film in the multilayer film is between 10 and 50 nm, the thickness of the TiN film in the multilayer film is between 50 and 450 nm, the sputtering pressure is between 0.1 and 0.6 Pa, and the sputtering gas is Ar; Preparation of the barrier layer: magnetron sputtering technology is used to deposit a Ti / TiN composite thin film barrier layer with a thickness of 50-500 nm on a pretreated stainless steel substrate. The sputtering gas is a mixture of Ar and N2, the sputtering pressure is between 0.1 and 0.6 Pa, and the sputtering power is 2 W / cm 2 .
3. The novel flexible copper indium gallium selenide thin film solar cell according to claim 1, characterized in that: The back electrode is a Mo:Na / Mo multilayer composite film, the thickness of the Mo:Na / Mo film in the multilayer film is 500nm, and the thickness of the Ti / TiN / Mo:Na / Mo multilayer structure film is between 300 and 1000nm; Preparation of the back electrode: Using magnetron sputtering technology, a 300-500nm Mo:Na / Mo composite film back electrode is deposited on the barrier layer; the sputtering gas is argon, the sputtering pressure is 10sccm, and the sputtering power is 2W / cm 2 .
4. The novel flexible copper indium gallium selenide thin film solar cell according to claim 1, characterized in that: The absorption layer is composed of a low-temperature copper indium gallium selenide absorption layer with a thickness of 0-80 nm and a high-temperature copper indium gallium selenide absorption layer with a thickness of 1800-2100 nm, and the low-temperature copper indium gallium selenide absorption layer is attached to the back electrode, and the high-temperature copper indium gallium selenide absorption layer is located outside the low-temperature copper indium gallium selenide absorption layer; Preparation of the absorption layer: first deposit a 0-80nm low-temperature copper indium gallium selenide absorption layer on the back electrode at room temperature, then heat it to 550-600 o C deposits a 1800~2100nm high-temperature copper indium gallium selenide absorber layer.
5. The novel flexible copper indium gallium selenide thin film solar cell according to claim 1, characterized in that: Preparation of the high resistance layer: A layer of intrinsic zinc oxide high resistance layer with a thickness of 80-120 nm is prepared on the buffer layer by magnetron sputtering, and the sputtering gas is one of Ar and N2 or a mixture of the two.
6. The novel flexible copper indium gallium selenide thin film solar cell according to claim 1, characterized in that: Preparation of the window layer: A 200-500nm thick aluminum-doped zinc oxide window layer is prepared on the high-resistance layer by magnetron sputtering, and the sputtering gas is one of Ar and N2 or a mixture of the two.
7. The novel flexible copper indium gallium selenide thin film solar cell according to claim 2, characterized in that: The substrate is a flexible stainless steel sheet with a thickness not exceeding 50 μm. The substrate is cleaned by using a roller brush and a cleaning agent for the first cleaning, a second cleaning with deionized water under ultrasonic waves, and finally drying the substrate with a hot air knife.
8. The novel flexible copper indium gallium selenide thin film solar cell according to claim 4, characterized in that: The absorption layer is made by sputtering a copper-indium-gallium-selenium composite single target, and the molar ratio of the copper, indium, gallium and selenium target materials is 22:18:8:
52.
9. The novel flexible copper indium gallium selenide thin film solar cell according to claim 4, characterized in that: During the sputtering of the CIGS absorption layer, a mixed gas of hydrogen and argon is introduced, and the hydrogen introduced is 4% of the argon flow rate.
10. The novel flexible copper indium gallium selenide thin film solar cell according to claim 1, characterized in that: The sputtering method used to prepare the magnesium-zinc-oxygen alloy thin film buffer layer is one or more of direct current sputtering, radio frequency sputtering and magnetron sputtering.